From macro to micro: slow-wave sleep and its pivotal health implications - Ishii, Toru; Taweesedt, Pahnwat Tonya; Chick, Christina F.; O'Hara, Ruth; Kawai, Makoto (Frontiers in Sleep, 2024)
Research on slow-wave sleep (SWS) began almost a century ago, not long after the discovery of electroencephalography. From maintaining homeostasis to memory function, the pivotal role of SWS in health has been established. The elucidation of its mechanisms and functions is directly related to the fundamental question of why people sleep. This comprehensive review first summarizes the basic science of SWS from anatomical and physiological aspects. It describes the fundamental mechanisms and functions of SWS, including hormonal regulation, developmental changes in SWS across the lifespan, and associations between SWS and optimal physical, psychological, and cognitive functions.Next, the relationship between SWS and physical and mental disorders, for which increasing knowledge has accumulated in recent years, is discussed from both research and clinical perspectives.Conditions such as memory impairment, sleep-disordered breathing, mood disorders, and neurodevelopmental disorders are of concern. The relationship between SWS and the glymphatic system, which is responsible for waste clearance in the brain, has also been explored, highlighting the potential neuroprotective role of SWS.Finally, we discuss the future direction of the field regarding whether interventions in SWS can improve health. We also address the problem of the inconsistent definitions of SWS, slow-wave activity, and slow oscillations. This review emphasizes the importance of discussing SWS from both macro-and microarchitectural perspectives and highlights its potential clinical and research impacts. By reviewing these aspects, we aim to contribute to a deeper understanding of SWS and the future development of this research field.